EFEKTIFITAS MODUL PEMBELAJARAN BIOLOGI MELALUI PENDEKATAN KONSTRUKTIVISME - Rona Taula Sari (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
Biology learning as one of subjects demand the understanding of concept, because in Biology learning, students are faced with abstact feature. Teachers need to lead student through the meaningful of learning. They experienced themselves. As a result, they can apply the knowledge in daily life. Thus, the use of biology learning which oriented constructivism approach is expected to increase students’ activities and learning outcomes. This research is the development of 3-D models (tree D). aims to produce learning modules ninth grade biology-oriented constructivism on the human reproductive system materials are effective. The technique analysis data of this research used validation sheet, practical and effective modules. The Data analysis techniques used in the form of descriptive data, by describing the practicality of using biological learning modules through a constructivsm approach. Based on the research result, it can be concluded that the learning module on biology material human reproductive system through a contructivist approach including effective categories consideration in terms of aspects student activities, student motivation, the result of learning.